Perceived Value as a Mediator: How Customer Experience Outweighs E-Service Quality in Driving Digital Repurchase Intention in Quick-Service Restaurants - Ardo Mohhanto; Muhadjir Anwar; Zainal Abidin Achmad; Thinzar Win (Universitas Pendidikan Nasional, 2025)
This study explores the different impacts of e-service quality and customer experience on repurchase intention, with perceived value as a mediator, among digital consumers of Yoshinoya quick-service restaurants in Surabaya, Indonesia. Using Structural Equation Modeling–Partial Least Squares (SEM-PLS) on data from 148 respondents, the results show that e-service quality does not significantly affect repurchase intention (coefficient = 0.166, p = 0.120), while customer experience has a strong direct effect (coefficient = 0.405, p < 0.001). Perceived value mediates the relationship between customer experience and repurchase intention (coefficient = 0.497, p < 0.001), but not between e-service quality and repurchase intention (coefficient = 0.074, p = 0.217). This study contributes to digital service and consumer behavior literature by showing that perceived value acts as a selective mediator, enhancing the impact of customer experience while reducing the role of e-service quality in technology-based QSR environments. Practically, the findings suggest that QSR managers should view e-service quality as a basic requirement and focus on experiential strategies, such as emotional engagement, personalization, and omnichannel consistency, to improve perceived value and maintain customer loyalty in competitive digital food service markets.